PENYELESAIAN KREDIT MACET DALAM PERBANKAN - Perbawa, I Ketut Sukawati Lanang Putra (Jurnal Advokasi, 2016)
Bad credit or loan is the credit problem experienced repayment difficulties due to the factors or elements of intentional or due to conditions beyond the ability of debtors. bad credit is highly feared by every bank, because it would interfere with the banks financial condition, may even result in the cessation of business activities of the bank. The emergence of non-performing loans including bad credit, basically does not occur suddenly, but through a process. Bad credit can be caused either by the creditors (banks) and debtors. If bad credit happens because the debtor does not carry out his achievements as contained in the credit agreement, then before execution collateral, the debtor must first be declared in default, which is done through a court decision. For the creditor must sue the debtor on the basis of default. But before suing the debtor, the creditor must first subpoena the contents so that the debtor fulfill his achievements. If the debtor does not also meet the performance, then the lender can sue the debtor on the basis wanpretasi, whereby if the court decides that the debtor was in default, then the lender can execute on the collateral provided by borrowers.